Performance assessment of major European ports an empirical investigation - Quintano, Claudio; Mazzocchi, Paolo; Rocca, Antonella (2021)
In the recent literature, the strategic relevance of ports has improved, and this paper provides a comparative analysis of 24 European ports. The port performance has been evaluated considering data envelopment analysis and Shephard’s distance function. This latter approach offers an alternative method to address a significant restraint of the standard Stochastic Frontier when the model needs to consider multiple outputs. From a policy point of view, the conclusion could offer valuable insights to support policy measures targeted to expand port efficiency. The findings obtained from the analysis reveal that several contextual indicators must be included in benchmark analysis.
Bibliografija: 77 jed.
Summary.
Keywords: Luke -- Položaj -- Učinkovitost; Europa